Nabi muhammad sang pembebas perempuan - Astuti, Sry (An - Nisa`, 2010)
this article study discusess about prophet muhammadâs role in lifting the degrre of women, this study is important, because till now still many criticism from west feminism activist, and also, there are some moslem assumed from west that islam are less esteeming religion for women, because in historylife if prophet of Muhammad as carrier of this religion, there were many events that indicated that exactly he is very persistent fight for and lift degree of women.As long as his wife, prophet Muhammad had become a combatant and emancipator of woman clan. He opposed vinicity tradition mainstay which is that time a very critic and tragic condition. He had oppesed heir right tradition just for body and do infinite women marry. He settled heir right tradition just for boy property. In short,Â  Prophet Muhammad proclaimed the same human being in front of God Allah, woman or man, and Arab people and non arab; all of them are same.